2014
DOI: 10.4081/or.2014.5405
|View full text |Cite
|
Sign up to set email alerts
|

Does intra articular platelet rich plasma injection improve function, pain and quality of life in patients with osteoarthritis of the knee? A randomized clinical trial

Abstract: We designed a randomized clinical trial with control group, to investigate the effects of platelet rich plasma (PRP) on pain, stiffness, function and quality of life in patients with knee osteoarthritis. Patients were randomly divided in two groups. For both groups of participants, therapeutic exercise was prescribed. In the PRP group, two courses of leukocyte rich PRP (5.6 fold higher platelet concentration) with a 4-week interval was injected. For each participant, Western Ontario and McMaster University’s A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 27 publications
(42 reference statements)
1
94
0
Order By: Relevance
“…Nine RCTs were included in the results, 15,16,[21][22][23][33][34][35]38 3 of which were double blinded ( Table 2). Hyaluronic acid was used for the control groups in 7 RCTs, saline was used in 1 study, and an exercise program was used in another.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine RCTs were included in the results, 15,16,[21][22][23][33][34][35]38 3 of which were double blinded ( Table 2). Hyaluronic acid was used for the control groups in 7 RCTs, saline was used in 1 study, and an exercise program was used in another.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…Other WOMAC and SF-36 (Short Form-36) parameters improved only in the PRP group. Another interesting RCT by Raeissadat et al 16 compared intraarticular PRP injections and a prescribed exercise program with a prescribed exercise program alone. After 6 months, the mean changes of total WOMAC, physical component summery, and mental component summery of SF-36 in the PRP group showed better improvement than the control group (P < 0.05).…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…There is experimental evidence for positive effects of PRP in the context of soft tissue healing, ligament and bone regeneration, and inflammation reduction [7][8][9][10]. In another study on Egyptian patients with lateral epicondylitis and with plantar fasciitis, PRP was found promising and effective in both [11].…”
Section: Introductionmentioning
confidence: 99%
“…61 In some in vitro and in vivo studies, antiinflammatory and reparative effects of PRP on cartilage, tendon, and ligament recovery have been shown. [62][63][64] The rationale for the use of Several studies have reported PRP to be clinically safe and effective in reducing pain following intra-articular injection of PRP up to 12 months following treatment. [66][67][68][69] Positive outcomes are mostly found more commonly in younger patients with Milles severe knee OA.…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%
“…61 In some in vitro and in vivo studies, antiinflammatory and reparative effects of PRP on cartilage, tendon, and ligament recovery have been shown. [62][63][64] The rationale for the use of PRP is to stimulate the natural healing cascade and tissue regeneration by release of platelet-derived factors directly at the site of treatment. …”
mentioning
confidence: 99%